Cambodia in 2017: descending into dictatorship? - Croissant, Aurel (Asian survey, 2018)
Skip to Next Section after local elections in 2017, the Cambodian People’s Party intensified its attacks on free media, NGOs, and the Cambodian National Rescue Party. Meanwhile, stronger links to China and waning Western leverage are enabling Prime Minister Hun Sen to transform the post-1993 multiparty system into a patrimonial dictatorship. Cambodia enjoyed strong economic growth but saw little improvement in its weak institutional framework, in social justice, or in economic competitiveness.
Gesehen am 24.01.2019
Keywords: Kambodscha; USA; China